1985
DOI: 10.1002/j.1939-4640.1985.tb00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Size: The Effects of Aging, Malnutrition, and Illness

Abstract: Paired testicular volumes and weights, as well as age, height, and weight, were recorded from a series of 1056 consecutive necropsies on adult males ranging in age from 18 to 96 years. These data were analyzed to examine the effects of age, nutritional state (standardized body weight), and illness on testicular size. Testicular volume and weight were related by a constant density of 1.038 g/ml, regardless of testicular size, age or illness. Mean testicular volume was correlated with height (r = 0.470), weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
0
7

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(85 citation statements)
references
References 35 publications
13
65
0
7
Order By: Relevance
“…These reported changes develop gradually without a sudden age threshold. Testicular volume decreases only towards the eighth decade 6 and in healthy men, it is 31% lower than in the 18-to 40-year age group. This change is accompanied by alterations in testicular histomorphology observed in older men.…”
Section: Testicular Function and Spermatogenesismentioning
confidence: 76%
See 1 more Smart Citation
“…These reported changes develop gradually without a sudden age threshold. Testicular volume decreases only towards the eighth decade 6 and in healthy men, it is 31% lower than in the 18-to 40-year age group. This change is accompanied by alterations in testicular histomorphology observed in older men.…”
Section: Testicular Function and Spermatogenesismentioning
confidence: 76%
“…3 There is a trend of age-related decline in daily sperm production per testis. 6 Semen volume and motility (evaluated both qualitatively and by computer-assisted sperm analysis method), tend to decrease with age. 15,16 In some studies, a paternal age-related decline in semen characteristics was not observed, but this is probably due to relative small numbers of older-aged men in the study population.…”
Section: Testicular Function and Spermatogenesismentioning
confidence: 99%
“…Testicular size (which is a rough indicator of spermatogenesis) is not, however, a relevant factor in age groups seeking fertility, as the specific effects of age alone demonstrated a reduction in testicular volume only in the eighth decade of life (Handelsman and Staraj, 1985).…”
Section: Paternal Age Testicular Morphology and Semen Parametersmentioning
confidence: 99%
“…31 Testis weights were not adjusted by weight or height or body surface area which might have accounted for these reported differences in testis volume. 32 Chinese and Caucasian men have less seminiferous tubular volume compared to Latino men; however, the length of seminiferous tubules per gram of parenchyma was greater in Chinese men than Latino or non-Latino Caucasian men. The volume per man of pachytene primary spermatocytes or spermatids nuclei was the lowest in Chinese men as well as the number of Sertoli cell per man; but the number of Sertoli cells per gram of parenchyma was lower in Latino men with no significant difference between Chinese or Caucasian men.…”
Section: Differences In Testicular Histomorphometrymentioning
confidence: 81%